Resilience and emotional intelligence in children with high-functioning autism spectrum disorder. (3rd May 2016) - McCrimmon, Adam W.; Matchullis, Ryan L.; Altomare, Alyssa A.
Abstract: Purpose : This article presents the results of an investigation of resilience factors and their relation to emotional intelligence (EI) as an area of potential strength for children with high-functioning autism spectrum disorder (HFASD). Based upon previous research with young adults, it was hypothesized that children with HFASD would demonstrate reduced EI and differential relations between EI and resilience as compared to typically developing (TD) children. Methods : Forty children aged 8–12 years (20 with HFASD and 20 TD control children) completed measures of resilience and EI. Results : Children with HFASD did not significantly differ from TD children on either measure. However, several significant correlations between resilience and EI were found in the HFASD sample. Conclusions : The findings suggest that EI may be a unique area of interest for this population, particularly for interventions that propose to capitalize upon potentially inherent strengths. Implications of these results for intervention are discussed.